2021
DOI: 10.12674/ptk.2021.28.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Roller Massage for Posterior Neck Muscles on the Muscle Strength and Range of Motion for Cranio-Cervical Flexion in Subjects With Forward Head Posture

Abstract: Cranio-cervical flexion Forward head posture Roller massage Suboccipital release Background: Forward head posture (FHP) causes various posture imbalances associated with the head and neck. Myofascial release is an effective treatment method used for relaxing muscles and reducing muscle hyperactivity, but no studies have been conducted on suboccipital and neck muscles related to FHP. Objects:The purpose of this study was to investigate the immediate effect of roller massages on the cranio-cervical flexion (CCF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Te role of manual therapy is limited in the treatment of headaches. Despite not being suitable for all forms of headaches, scientifc evidence supports the use of a few manual therapies, such as cervical spinal exercises, spinal joint mobilization and manipulation, trigger point therapy, physical therapy using heat and cold packs, ultrasound, electrical stimulation, massage, acupuncture, and cognitive pain approaches, which are based on a nociceptive pain theory and aim to modulate central nervous system hypersensitivity, in the treatment of tension-type and cervicogenic headaches [22][23][24][25][26][27][28]. It has been demonstrated that passive cervical spine mobility or manipulation is useful in lowering or alleviating CGH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te role of manual therapy is limited in the treatment of headaches. Despite not being suitable for all forms of headaches, scientifc evidence supports the use of a few manual therapies, such as cervical spinal exercises, spinal joint mobilization and manipulation, trigger point therapy, physical therapy using heat and cold packs, ultrasound, electrical stimulation, massage, acupuncture, and cognitive pain approaches, which are based on a nociceptive pain theory and aim to modulate central nervous system hypersensitivity, in the treatment of tension-type and cervicogenic headaches [22][23][24][25][26][27][28]. It has been demonstrated that passive cervical spine mobility or manipulation is useful in lowering or alleviating CGH.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that passive cervical spine mobility or manipulation is useful in lowering or alleviating CGH. Following mobilization treatment, there are improvements in headache frequency, duration, and intensity, and a decrease in the need for headache pain medication has been recorded [25][26][27][28][29]. Although it has not been demonstrated that muscular tightness is a signifcant component of CGH, CGH has been linked to limits in cervical muscle strength, endurance, performance, and control [7,20,29,30].…”
Section: Introductionmentioning
confidence: 99%